Analisis Perbandingan Metode Defuzzifikasi Fuzzy Inference System Mamdani Dalam Penentuan Produksi Tua Kolo (Sopi Timor) 45% Pada Pabrik Sane Up-Ana Kefamenanu - Sansela Neonbeni; Grandianus Seda Mada; Fried Markus Allung Blegur (Fakultas Pertanian, Universitas Timor, 2022)
Tua Kolo (Timor Sopi) is one of the local alcoholic products that is closely related to the culture of the Timorese people. This drink is often used in various cultural events such as weddings, funerals, etc. Tua Kolo is made from palm sap and is traditionally processed through fermentation and distillation. The Sane Up-ana factory is one of the factories in Timor that produces Tua Kolo. Factory production levels are not always fixed in each period, where consumer demand changes every month and even every day so factories are sometimes unable to meet market demand due to increased demand and lack of supplies. Uncertainty in determining the amount of production causes losses to the factory so that a method is needed that can optimize the amount of production so that the factory's profits could increase. The method that can be used to determine decisions based on data uncertainty is the Fuzzy Inference System (FIS). This method is based on the concept of fuzzy logic. One of the most frequently used FIS methods in determining the amount of production is the Mamdani FIS method. The process of determining the final decision with this method has several stages, namely fuzzification, the application of the implication function, rule composition, and defuzzification. For the defuzzification stage, there are five methods that can be used, namely the Centroid method, the Bisector method, the Mean Of Maximum (MOM) method, the Smallest Of Maximum (SOM) method, and the Largest Of Maximum (LOM) method. This study aims to determine the amount of production of Tua Kolo 45% by considering demand, product supply, and raw material supply. To obtain optimal results, we will first investigate the best defuzzification method to be used in the system. In determining the best defuzzification method, the Mean Absolute Percentage Error (MAPE) measure is used. The results showed that the centroid is the best defuzzification method with a prediction error rate of 18.95% or an accuracy level of 81.05% therefore it can be concluded that the centroid method is very suitable for producing Tua Kolo (Sopi Timor) at the Sane Up-ana Kefamenanu Factory.